MATHEMATICAL AESTHETICS OF JEPARA'S CARVING - Fitria Utami, Rahmi Nur; Muhtadi, Dedi; Hermanto, Redi (Journal of Authentic Research on Mathematics Education (JARME), 2023)
Jepara's carving is a work of art with a mathematical concept of aesthetic value. Mathematical aesthetics refers to the relationship between mathematics and aesthetic values, namely the beauty of mathematics integrated with the art of Jepara's carving. The qualitative descriptive method is used to describe aesthetics and mathematical concepts in Jepara's carving and the relationship between the two focuses of the study. Data were collected using semi-structured interviews, non-participatory observation, and documentation. The research subjects consisted of two informants: art and culture teachers and Jepara's carving artisans. The data were analyzed using the Miles and Huberman model, which consisted of the following stages: data reduction, data presentation, and conclusion drawing. The results showed that: (1) Jepara's carving has aesthetic value, seen from the fulfillment of aesthetic elements, namely: unity, complexity, sincerity, and balance; (2) the process of making Jepara's carving applies the mathematical concept of comparison, which plays an essential role in making Jepara's carving patterns; and (3) there is a collaboration between the application of mathematical concepts and aesthetic theory in creating the term mathematical aesthetics in Jepara's carving which refers to geometric aesthetics, wherein this Jepara's carving motif there is a regularity of patterns dominated byÂ  Â .